Romantyczność 2022 - rocznicowe obrachunki i wyzwania współczesności = Romantyczność 2022 - anniversary summing-up and contemporary challenge - Wawryk, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses the literary works from Romantyczność 2022 almanac as "contemporary ballads and romances" inspired by the works of Adam Mickiewicz. For the writers, Romanticism is still a living tradition and they refer to it in quotations, allusions, travesties, characters or motifs.
Keywords: romantyzm; romantyczność; Mickiewicz, Adam (1798-1855). Ballady i romanse; tradycja literacka; współczesność; romanticism; romance; Mickiewicz, Adam (1798-1855). Ballades and romances; literary tradition; contemporary times